(untitled) (Research, Society and Development, 2020)
The present work aims to apply the slow pasteurization process to the pulp and skin of the mandacaru fruit and to evaluate its influence on total phenolic compounds and antioxidant activity. Manual pulping was performed to obtain the fractions of the mandacaru fruit, where the pulp and skin were separated. Then, the fractions obtained were processed in a domestic blender and packed separately in glass containers where they were pasteurized by immersion in water at 65 °C for 30 minutes. Therefore, the parameters of total phenolic compounds and antioxidant activity were analyzed by the ability to capture the ABTS+ (2.29-azinobis-(3-etilbenzotiazolina-6-sulfônico) radical and the ability to capture the DPPH (2.2-difenil-1- picril-hidrazil) radical. The highest values of bioactive compounds were found for the peel of the mandacaru fruit. There was a concentration of phenolic compounds for mandacaru peel and degradation of antioxidant activity due to the pasteurization process for both fractions analyzed, except for the analysis of DPPH for the pulp. As suggestions for future work, the pasteurization kinetics of the product can be made by obtaining its thermophysical parameters, in addition to evaluating the effect of this treatment during the storage of the fractions.